Incidence of insect pest on shorea macrophylla and dryobalanops beccarii at Gunung Apeng Reforestation area, Sarawak - Elfera, Polly (Universiti Malaysia Sarawak(UNIMAS), 2016)
Incidence of insect pest in Shorea macrophylla (Engkabang jantong) had a critical leaf damage compare to Dryobalanops beccarii (Kapur bukit) in monoculture planting. The main objectives are to assess the leaf damage and influence the damages by tree ages, light intensity and relative humidity. This study was conducted at Gunung Apeng to assess the leaf damage tree of Engkabang jantong and Kapur bukit planted in the enrichment planting by line planting technique in the disturbed secondary forest. The light intensity was measured using light meter and converted to percentage while relative humidity was taken using whirling hygrometer and change to percentage using relative humidity table. The result showed that the degree of leaf damage decrease with the age of the Engkabang jantong tree. In average, the leaf damage of Engkabang jantong is 45.06%. Leaf damage of Engkabang jantong caused by insect pest was highly occurred high light intensity and high relative humidity. Leaf damage of Kapur bukit was significantly very low with average 0.89% damages. The age stand, light intensity and relative humidity did not affect the leaf damage of Kapur bukit attacked by insect pest. The common leaf damages on Engkabang jantong tree was ‘hole damage’ caused by insect order Lepidoptera, while Kapur bukit tree with folded leaf damage. In this case, Kapur bukit (Dryobalanops beccarii) was the most suitable species as compared to Engkabang jantong (Shorea macrophylla) for a reforestation programme using enrichment line planting in term of low leaf damage caused by insect pest attack at different stand ages, light intensity and relative humidity.